Krukenberg tumor in a young woman: A rare presentation - Deepa Hatwal; Chitra Joshi; Sheela Chaudhari; Pawan Bhatt (Wolters Kluwer Medknow Publications, 2014)
Krukenberg tumors mostly occur after 40 years. Metastatic ovarian tumors in young age are very rare and reported to be 2% of all the cases. Thirty percent of all ovarian neoplasms occurring during childhood and adolescence are malignant. A 25-year-old woman, parity- 2, presented with abdominal distension, pain in abdomen and amenorrhea. On examination, 18 weeks lump was palpable, firm to hard in consistency, non-tender and mobile. On ultrasonography bilateral ovarian tumors were reported, without any peritoneal free fluid. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. Microscopic examination revealed signet ring cells with glandular differentiation, diffusely invading the ovarian parenchyma. Tumor cells exhibited strong, diffuse immunopositivity for CEA with focal strong immunopositivity for CK7 and CK20 and immunonegativity for SATB2. Diagnosis of Krukenberg tumor was made. Endoscopic biopsy confirmed the diagnosis of adenocarcinoma stomach. This case is reported because of its rarity in younger age group.